2006
DOI: 10.1063/1.2186517
|View full text |Cite
|
Sign up to set email alerts
|

Metal gate work function engineering using AlNx interfacial layers

Abstract: Metal gate work function enhancement using thin AlNx interfacial layers has been evaluated. It was found that band edge effective work functions (∼5.10eV) can be achieved on hafnium-based high dielectric constant (high-k) materials using the AlNx interfacial layer and TiSiN electrodes. It was also found that the effective work function enhancement by the AlNx interfacial layer increased when the concentration of SiO2 in the gate dielectric was increased. Thus, the enhancement was minimal for HfO2 and maximum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 2 publications
2
42
0
Order By: Relevance
“…It has been reported that both Al and rare earth metals show significant diffusion in Hf-based gate stacks. 1,5,9 Upon diffusion, the aluminum and rare earth metals were found to react with the gate dielectric and interfacial SiO 2 layers. Some studies suggested the formation of silicates such as LaSiO x at the interface near the substrate, 14 while others indicated the formation of a HfLaSiO gate dielectric as a result of these reactions.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both Al and rare earth metals show significant diffusion in Hf-based gate stacks. 1,5,9 Upon diffusion, the aluminum and rare earth metals were found to react with the gate dielectric and interfacial SiO 2 layers. Some studies suggested the formation of silicates such as LaSiO x at the interface near the substrate, 14 while others indicated the formation of a HfLaSiO gate dielectric as a result of these reactions.…”
Section: à3mentioning
confidence: 99%
“…Experimental and theoretical investigation of the effect of SiO 2 content in gate dielectrics on work function shift induced by nanoscale capping layers [3][4][5] and rare earth metal-based capping layers. 1,6,7 The composition of the capping layer, its thickness, and thermal budget used to fabricate devices incorporating such capping layers have all been thoroughly studied.…”
mentioning
confidence: 99%
“…[1][2][3] It is used in metal gate complementary metal oxide devices as a dipole layer to shift the flatband voltage for p-type metal oxide semiconductor ͑pMOS͒ transistors. 4 These applications require a knowledge of its electronic defect levels in order to explain its transport and charge trapping properties. [5][6][7][8] Electron transport in Al 2 O 3 is consistent with Poole-Frenkel hopping in a deep state lying at ϳ1.8 eV below the conduction band ͑CB͒ edge.…”
mentioning
confidence: 99%
“…An alternative way to control the band alignment (and the threshold voltage) would be to develop a gate stack where one can effectively modify the position of the Fermi level of the metal [6,7]. Experimental attempts of adjusting the Fermi level include doping the gate dielectrics stack, which includes an HfO 2 -based film and a thin layer of SiO 2 (which either spontaneously forms at the interface with the Si substrate or is intentionally grown), with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, group III metals have been suggested to modify the interfacial dipole. For example, La has been used for the n-type silicon field effect transistors (FETs) [6,[8][9][10][11] and Al for the p-type FETs [7,[12][13][14][15][16][17]. The doping can be achieved, for instance, via the ion diffusion from a thin metal oxide capping layer deposited on top of the HfO 2 -based dielectric.…”
Section: Introductionmentioning
confidence: 99%